Mali - Land, climate, energy, agriculture and development: A study in the Sudano-Sahel Initiative for regional development, jobs, and food security - Ousmane Coulibaly (University of Bonn, Center for Development Research (ZEF), 2021)
Mali is a Sub-Saharan African country with 19.1 million people. Almost half of this population lives in poverty, due to the dysfunction of activity sectors (agriculture, energy, education, employment, services, etc.). Natural resource management especially land and water together with corollaries remain one of the greatest challenges for this dryland region to sustainably face climate change, meet food demand and improve its economy. The social crisis (especially in the northern region) is significantly affecting development and human security as well. This study had been carried out to review the current state of affairs, key trends, problems, solutions and their implications for sustainable development of Mali under changing climate and the impacts of land degradation. Likewise, investment opportunities in the priority areas are highlighted in this report.
Keywords: O1; O2; O3; Q1; Q2; Q4; Q5; J43; 330; Mali; poverty; agriculture; economy; climate change; land degradation; sustainable development